2011
DOI: 10.1017/s0317167100011902
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Randomized Trials on First Line and Adjunctive Levetiracetam

Abstract: Levetiracetam, a pyrrolidine, the racemically pure Senantiomer of pyrrolidineacetamide, is an antiepileptic medication with a novel mechanism, related to a specific binding site in the brain for the synaptic vesicle protein 2A 1 . In contrast to the mechanism of traditional antiepileptics, there is no evidence for action on voltage-gated sodium channel, gammaamino butyric acid, or glutamate-mediated synaptic transmission 2 . Levetiracetam has a linear pharmacokinetic profile, high oral bioavailability (close t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
(11 reference statements)
0
21
0
Order By: Relevance
“…Lo BW et al [22] performed another meta-analysis of 10 RCTs: the likelihood of serious AEs requiring withdrawal from the study was not significantly different between LEV patients and controls (RR= 1.37; 95% CIs 0.88 to 2.13). The meta-analysis of Zaccara et al [51] was performed on 5 RCTs and found only somnolence being associated with LEV (RD 0.07; 95% CIs 0.01 to 0.12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lo BW et al [22] performed another meta-analysis of 10 RCTs: the likelihood of serious AEs requiring withdrawal from the study was not significantly different between LEV patients and controls (RR= 1.37; 95% CIs 0.88 to 2.13). The meta-analysis of Zaccara et al [51] was performed on 5 RCTs and found only somnolence being associated with LEV (RD 0.07; 95% CIs 0.01 to 0.12).…”
Section: Discussionmentioning
confidence: 99%
“…Different randomized controlled trials (RCTs) and some meta-analyses [22,24,26] have shown a good safety profile for this drug.…”
mentioning
confidence: 99%
“…LEV is considered to be an effective add-on treatment across various seizure types in patients with refractory epilepsy. 25 The PWE in this study were prescribed LEV as adjunctive treatment and converted to monotherapy when possible. LEV monotherapy, monitored with blood levels, was more effective than was LEV with polypharmacy and demonstrated reduced concentration/dose ratio.…”
Section: Discussionmentioning
confidence: 99%
“…In paediatric cohorts, the proportion of such adverse events was 20% to 30%. [70][71][72]94 By comparison, the behavioural sideeffects in adults were less prominent.…”
Section: Levetiracetammentioning
confidence: 94%